Factors That Affect Motivasi Training PPLP Boxing Athletes During The Covid-19 Pandemic In Palu City - Zahra Zetira; Tandiyo Rahayu; Soedjatmiko Soedjatmiko (STKIP Muhammadiyah Kuningan, 2023)
The objectives of this study: (1) How to find out the training motivation of PPLP boxing athletes during the Covid-19 pandemic in Palu City; (2) How to maintain the intrinsic motivation of PPLP boxing athletes during training during the COVID-19 pandemic in Palu City; (3) How to maintain the extrinsic motivation of PPLP boxing athletes during training during the COVID-19 pandemic in Palu City; (4) What obstacles do PPLP boxing athletes face during training during the COVID-19 pandemic in Palu City. The research uses qualitative methods with the design of phenomenological studies. The data source is information from PPLP athletes from Central Sulawesi Province, coaches, provincial dispora and parents of PPLP boxing athletes. The data obtained are analyzed qualitatively with the following steps: (1) data collection; (2)data reduction; (3) presentation of data. The results showed that the training conditions of pplp boxing athletes during the Covid-19 pandemic in Palu city felt the influence of the Covid-19 pandemic from the beginning of appearing in Central Sulawesi in 2020. The obstacle to training pplp boxing athletes during the Covid-19 pandemic in Palu city is that during this pandemic, the government issued a very unprofitable policy for PPLP boxing athletes. The training strategies for boxing athletes during the covid-19 pandemic in the city of Palu can still train during the pandemic; they are restricting training grounds. Online media is a solution for PPLP Central Sulawesi boxing athletes; by using online media, they can carry out training through the program provided by the trainer and not carry out training in crowded places.